Coordination-Driven Poly[2]Pseudorotaxanes in Highly Polar Organic Solvent - Su, Hang; Chen, Wei; Li, Liang; Li, Bin; Zhang, Zhi-Yuan; Li, Chunju (Frontiers in Chemistry, 2020)
Self-assembly of polypseudorotaxanes in high-polar solvents is difficult due to remarkably weak interactions between macrocycles and axles. Reported here is a novel metal-coordinated poly[2]pseudorotaxane constructed by pillar[5]arene, 1,4-bis(4-pyridyl pyridinium)butane, and [PdCl2(PhCN)2] in highly polar organic solvent of dimethyl sulfoxide (DMSO). Utilizing a combination of 1H NMR, NOESY, DOSY, DLS, SEM and Viscosity measurements, the formation of polypseudorotaxane was shown to be dependent on the concentration of [2]pseudorotaxanes/[PdCl2(PhCN)2] and temperature. Furthermore, a temperature-responsive supramolecular gel with reversibly gel–sol transformation was obtained via spontaneous assembly of the polypseudorotaxane at high concentration.